Renal vascular TRP channels - Kanthakumar, Praghalathan; Adebiyi, Adebowale (Current research in physiology, 2021)
Members of the transient receptor potential (TRP) channels that are expressed in the kidney have gained prominence in recent years following discoveries of their role in maintaining the integrity of the filtration barrier, regulating tubular reabsorption of Ca2+ and Mg2+, and sensing osmotic stimuli. Furthermore, evidence has linked mutations in TRP channels to kidney disease pathophysiological mechanisms, including focal segmental glomerulosclerosis, disturbances in Mg2+ homeostasis, and polycystic kidney disease. Several subtypes of TRP channels are expressed in the renal vasculature, from preglomerular arteries and arterioles to the descending vasa recta. Although investigations on the physiological and pathological significance of renal vascular TRP channels are sparse, studies on isolated vessels and cells have suggested their involvement in renal vasoregulation. Renal blood flow (RBF) is an essential determinant of kidney function, including glomerular filtration, water and solute reabsorption, and waste product excretion. Functional alterations in ion channels that are expressed in the endothelium and smooth muscle of renal vessels can modulate renal vascular resistance, arterial pressure, and RBF. Hence, renal vascular TRP channels are potential therapeutic targets for the treatment of kidney disease. This review summarizes the current knowledge of TRP channel expression in renal vasculature and their role in controlling kidney function in health and disease. [Display omitted] •TRP channels are widely distributed in mammalian kidneys in glomerular, tubular, and vascular cells.•TRPC and TRPV channels are functionally expressed in afferent arterioles.•TRPC4 may regulate Ca2+ signaling in the descending vasa recta.•Smooth muscle, endothelial, and pericyte TRP channels may participate in signal transduction mechanisms.•TRP channels underlie renal autoregulation and regional kidney perfusion in health and disease.